Paleoenvironmental evolution and evidence of marine submersion events from mid-to late Holocene in northwestern Morocco: The case of the Tahaddart lower estuary. (1st March 2023) - Khalfaoui, Otmane; Dezileau, Laurent; Mojtahid, Meryem; Degeai, Jean-Philippe; Snoussi, Maria; Araya, Karen
Abstract: The present study aims at reconstructing mid-to late Holocene paleoenvironmental evolution of the Tahaddart lower estuary (NW of Morocco) and to find possible sedimentary evidence of past marine submersion events (storm surges and tsunamis). This is achieved through the study of four sedimentary cores and by using a multiproxy approach that combines sedimentological, geochemical and foraminiferal analyses. Radioisotope measurements of 210 Pbex, 137 Cs and 14 C were used to provide a chronological framework of the studied cores. The results show that the Tahaddart lower estuary has evolved from a bay-like environment characterized by very shelly sandy facies (i.e., marine phase) between ∼6800 and ∼625 cal BP, to an estuarine system after ∼625 cal BP, with a dominance of fine-grained sediments (i.e., estuarine phase). We further identified several sedimentary deposits that we interpret as possible marine submersion events. Two events were identified in the marine phase at ∼3800 cal BP and ∼2700 cal BP, in coherence with previously documented marine high-energy deposits located on the Atlantic Iberian coast. In the estuarine phase of the cores, two other events were detected and dated at ∼625 cal BP and ∼200 cal BP. The latter coincides with the 1755 CE Lisbon tsunami (195 cal BP). Highlights: Four sediment cores are extracted from the Tahaddart lower estuary. The studied area was a bay-like environment between ∼6800 and ∼625 cal BP. Four marine submersion events are identified, including the 1755 CE Lisbon tsunami.